Metabolic reconfiguration of the central glucose metabolism: a crucial strategy of Leishmania donovani for its survival during oxidative stress. Issue 5 (17th February 2015) - Ghosh, Ayan K.; Sardar, Abul H.; Mandal, Abhishek; Saini, Savita; Abhishek, Kumar; Kumar, Ashish; Purkait, Bidyut; Singh, Ruby; Das, Sushmita; Mukhopadhyay, Rupkatha; Roy, Syamal; Das, Pradeep
ABSTRACT: Understanding the mechanism that allows the intracellular protozoan parasite Leishmania donovani ( Ld ) to respond to reactive oxygen species (ROS) is of increasing therapeutic importance because of the continuing resistance toward antileishmanial drugs and for determining the illusive survival strategy of these parasites. A shift in primary carbon metabolism is the fastest response to oxidative stress. A 14 CO2 evolution study, expression of glucose transporters together with consumption assays, indicated a shift in metabolic flux of the parasites from glycolysis toward pentose phosphate pathway (PPP) when exposed to different oxidants in vitro/ex vivo. Changes in gene expression, protein levels, and enzyme activities all pointed to a metabolic reconfiguration of the central glucose metabolism in response to oxidants. Generation of glucose‐6‐phosphate dehydrogenase (G6PDH) (~5‐fold) and transaldolase (TAL) (~4.2‐fold) overexpressing Ld cells reaffirmed that lethal doses of ROS were counterbalanced by effective manipulation of NADPH:NADP + ratio and stringent maintenance of reduced thiol content. The extent of protein carbonylation and accumulation of lipid peroxidized products were also found to be less in overexpressed cell lines. Interestingly, the LD50 of sodium antimony gluconate (SAG), amphotericin‐B (AmB), and miltefosine were significantly high toward overexpressing parasites. Consequently, this study illustrates that Ld strategizes a metabolic reconfiguration for replenishment of NADPH pool to encounter oxidative challenges.—Ghosh, A. K., Sardar, A. H., Mandal, A., Saini, S., Abhishek, K., Kumar, A., Purkait, B., Singh, R., Das, S., Mukhopadhyay, R., Roy, S., Das, P. Metabolic reconfiguration of the central glucose metabolism: a crucial strategy of Leishmania donovani for its survival during oxidative stress. FASEB J. 29, 2081‐2098 (2015). www.fasebj.org